2017
DOI: 10.1038/eye.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to assess the ‘treat-and-extend’ dosing regimen for neovascular age-related macular degeneration using ranibizumab

Abstract: Age related macular degeneration (AMD) is the leading cause of irreversible blindness in the developed world. Monthly or as-needed (PRN) dosing strategies of intravitreal ranibizumab have been established as efficacious treatment options for neovascular AMD. More recently, the "Treatand-Extend" dosing regimen (TREX) is being adopted in clinical practice as it represents a patientcentric and economical option, reducing treatment burden by extending injection intervals when possible. However, the efficacy of TRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 32 publications
0
49
0
Order By: Relevance
“…In a recent meta-analysis, T&E using ranibizumab was shown to be superior to PRN and as effective as monthly dosing in improving visual acuity outcomes, 46 with a weighted frequency of 8.6 injections in 1 year. 47 The worst T&E profile, which is associated with a high number of injections required in the first 12 months of treatment, is similar to a monthly dosing regimen. The worst T&E profile in this study was based on the available data at the time of the study, which included the Trex-AMD and LUCAS trials.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, T&E using ranibizumab was shown to be superior to PRN and as effective as monthly dosing in improving visual acuity outcomes, 46 with a weighted frequency of 8.6 injections in 1 year. 47 The worst T&E profile, which is associated with a high number of injections required in the first 12 months of treatment, is similar to a monthly dosing regimen. The worst T&E profile in this study was based on the available data at the time of the study, which included the Trex-AMD and LUCAS trials.…”
Section: Discussionmentioning
confidence: 99%
“…Both RCTs and retrospective studies using the TAE/TES method have demonstrated superior visual outcomes compared to PRN studies. In a systematic review by Rufai et al, which included the assessment of 748 eyes undergoing the TAE protocol, the one-year BCVA improvement was 8.9 letters, compared to the 3.5 letters reported by Chin-Yee et al in a separate systematic review regarding the PRN method [51]. Head to head studies, such as those by Chin-Yee et al, demonstrated an average 10.4 letter improvement in the TAE group vs. 5.4 letters in the PRN group at 12 months, with the TAE group receiving about 3.5 more injections on average [52].…”
Section: Treat-and-extend (Tae) and Treat-extend-stop (Tes) Methodsmentioning
confidence: 84%
“…Today, we often diagnose CNV, decide whether to perform the anti-VEGF treatment and monitor the effect of treatments according to OCT scans [20], because it is safe, quick and non-invasive [12]. Morphological improvement in OCT, which shows recovery of the foveal contour, indicates a good prognosis and better recovery of retinal function [21].…”
Section: Discussionmentioning
confidence: 99%